2018
DOI: 10.1016/j.stemcr.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 Deficiency Contributes to Mandibular Dysplasia by Upregulating MMP3

Abstract: SummarySkeletal mandibular hypoplasia (SMH), one of the common types of craniofacial deformities, seriously affects appearance, chewing, pronunciation, and breathing. Moreover, SMH is prone to inducing obstructive sleep apnea syndrome. We found that brain and muscle ARNT-like 1 (BMAL1), the core component of the molecular circadian oscillator, was significantly decreased in mandibles of juvenile SMH patients. Accordingly, SMH was observed in circadian-rhythm-disrupted or BMAL1-deficient mice. RNA sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 68 publications
3
29
0
Order By: Relevance
“…Takarada et al also found the body length measured from nose to anus and the longitudinal lengths of both tibia and femur decreased remarkably in BMAL1‐deficient mice than wild‐type mice . Our previous study also demonstrated that osteogenic differentiation is reduced in limb and mandible from Bmal1 ‐/‐ mice . Unlike the limb bone and maxillary and mandibular body which mainly rely on intramembranous osteogenesis, MCC is considered as a secondary cartilage and has significant structural differences from primary cartilages .…”
Section: Discussionsupporting
confidence: 54%
“…Takarada et al also found the body length measured from nose to anus and the longitudinal lengths of both tibia and femur decreased remarkably in BMAL1‐deficient mice than wild‐type mice . Our previous study also demonstrated that osteogenic differentiation is reduced in limb and mandible from Bmal1 ‐/‐ mice . Unlike the limb bone and maxillary and mandibular body which mainly rely on intramembranous osteogenesis, MCC is considered as a secondary cartilage and has significant structural differences from primary cartilages .…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, OPG‐deficient male mice can serve as a model for studying severe alveolar bone loss . We previously deployed a protein chip analysis and found that OPG expression in the mandible was decreased significantly in Bmal1 −/ − mice compared with wild‐type mice …”
Section: Introductionmentioning
confidence: 99%
“…All mice were maintained under 12/12-h light/dark cycles with the light on from 8:00 a.m. (Zeitgeber time 0, ZT0) to 8:00 p.m. (ZT12) and fed antibiotic-free food and water ad libitum . In the experiment, C57BL/6J mice were placed on a previously described jet-lagged schedule with 8-h light advanced every 2–3 days for 12 weeks, which mimicked the circadian disturbance that humans undergo during shift work (Zhao et al, 2017 ). PT was mildly shortened, while APTT was significantly prolonged, and the fibrinogen reaction time was shortened owing to elevated plasma fibrinogen in jet-lagged mice ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%